A Qualitative Pilot Study on Donation After Cardiac Death (DCD): Feelings Experienced by the Nursing and Medical Staff in the Adult Intensive Care Unit (ICU) of the Geneva University Hospitals. (August 2017) - Zellweger, Alessia; Gasche, Yvan; Moretti, Diane; Majmou, Hasna; Cedraschi, Christine
Abstract : Aim: DCD is considered a viable solution to reduce organ shortage, but it raises serious ethical and psychological issues that cannot be ignored. Understanding what alters DCD acceptance by ICU caregivers is important to run a sustainable DCD program and to offer an adapted support for the personnel involved. The aim of our research was to shed new light on feelings experienced by caregivers when involved in DCD. Methods: We conducted an exploratory qualitative study before the introduction of DCD to investigate how ICU caregivers at the Geneva University Hospitals perceive DCD and how they associate this practice to ethical interrogations. Our qualitative study was based on three semi-structured focus groups with a sample of twenty-four caregivers (nurses, physicians and care assistants). Results: Our analysis of caregivers' feelings toward DCD showed the presence of various stress factors which are perceived as potential barriers to DCD acceptance. The temporal proximity between therapeutic withdrawal decision and organ donation process introduces a sense of "conflict of duty" in caregivers. Brain death not being central in DCD, traditional landmarks in donation are lost, which makes caregivers uncomfortable with this procedure. Some ICU professionals are afraid of families' and public's judgment. Some of them may perceive incoherence between social desirability and individual values. Taking into account all these issues, we can also observe that the majority of caregivers are able to deal with these complexities; they do not reject DCD but on the contrary they made several suggestions which are intended to reduce psychological impact of DCD, such as a desire of objectivity regarding DCD criteria or the training of specialised professionals to achieve DCD process. They stated being in favour of organ donation and in addition, we also observe trust in the DCD program and a high level of support within ICU. Conclusion: Our qualitative study highlights major psychological distress induced by DCD, which represents a potential barrier to DCD acceptance in ICU. However, we can also observe that caregivers are able to deal with DCD difficulties by proposing solutions which are intended to reduce its psychological impact. In view of our results, we can consider if the introduction of DCD in the ICU should be accompanied by a program of psychological support to help caregivers dealing with this new and demanding activity. A pilot study on the feelings experienced by the nursing and medical staff in the adult intensive care unit (ICU) of the Geneva University Hospitals. This study was financially supported by the Department of Anaesthesiology, Pharmacology and Intensive Care Medicine Research Fund. The Geneva University Hospital DCD program is financially supported by the Geneva University Hospitals Private Foundation. We also gratefully acknowledge the support of Dynèle Gautier and also all the adult intensive care unit who has always been highly collaborative .